A Model for Accommodation Selection using GIS and Multi Criteria System (Global Journal of Human-Social Science, 2018)
The main purpose of this research to develop a preference model for the best accommodation selection process in Chittagong city Bangladesh based on College Market Hospital and Park with GIS and Multi-Criteria System MCS A decision is the result of a comparison of one or more alternatives concerning one or more criteria that we considered relevant for the task at hand MCS is primarily concerned with how to combine the information from Multi- Criteria to form a single index of evaluation Multi-Criteria System MCS provides a more logical and scientific way for best accommodation selection MCS describes any structured approach used to determine overall preferences among alternative options where accomplish several criteria The results were having a sample of the computerized program that could be used to measure these indicators and their weights The integration of multi-criteria evaluation MCE and multi-criteria decision making MCDM techniques with the Geographical information system GIS are forward as providing the user with the means to evaluate various alternatives by multiple and collecting criteria These criteria are Market Office Rood Park Sea beach Hospital University College School Mosjid Mondir Temple Playground Airport and Police station There is a most important option is weight The weights for the multi-criteria system obtained from the multiple criteria For a selection of the best suitable location for accommodation there were a lot of elements that should take into some consideration The people who want to live in this location which provides their own facility in Chittagong city Bangladesh they can search their best accommodation by this work So people must save their time to get an appropriate location for this work So as a result the select a best accommodation considered by the multi-criteria The research work has been done based on some development area of Chittagong city in Bangladesh